The Influence of Law Number 16 of 2019 concerning the Age of Marriage in the Culture of the Madura Tribal Community in Banyuwangi Regency - Ansari, Ansari (Civiliza Publishing, 2024)
Early marriage is still a significant problem in Indonesia, including in Banyuwangi Regency, especially among the Madura people. Although Law Number 16 of 2019 sets a minimum marriage age limit of 19 years to protect the rights of children and women, early marriage still occurs, mainly due to cultural factors. This study aims to analyze the influence of the implementation of Law Number 16 of 2019 on the marriage culture in the Madura community, as well as to understand the perception of the younger generation towards this regulation and identify the problems that arise after the enactment of the law. The research method uses field research , with an empirical juridical approach. The results of the study show that Law No. 16 of 2019 aims to reduce early marriage, its implementation in the field is experiencing obstacles. The Madura people in Banyuwangi, who are still very steeped in the tradition of young marriage, tend to show resistance to the new rules. Many families still view early marriage as part of social norms and traditions. However, a number of parties, especially the younger generation and religious leaders, are beginning to realize the importance of this rule and there is a change in attitude towards a more mature marriage age.